2021
DOI: 10.1371/journal.pone.0250062
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to recurrent episodes of acute decompensation/acute-on-chronic liver failure characterizes those triggered by indeterminate precipitants in patients with liver cirrhosis

Abstract: Background Acute decompensation (AD) of liver cirrhosis (LC) and subsequent acute-on-chronic liver failure (ACLF) are fatal and impair quality of life. Insufficient knowledge of the highly heterogeneous natural history of LC, including decompensation, re-compensation, and possible recurrent decompensation, hinders the development and application of novel therapeutics. Approximately 10%-50% of AD/ACLF is reported to be precipitated by any indeterminate (unidentifiable, cryptogenic, or unknown) acute insults; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…triggers do not have any clinically identifiable cause (21)(22)(23). The mechanism of inflammation is not very well-characterized.…”
Section: Pathophysiological Mechanisms In Aclf Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…triggers do not have any clinically identifiable cause (21)(22)(23). The mechanism of inflammation is not very well-characterized.…”
Section: Pathophysiological Mechanisms In Aclf Systemic Inflammationmentioning
confidence: 99%
“…Systemic inflammation may occur in the presence and absence of identifiable and non-identifiable triggers. Identifiable triggers may include bacterial infections, excessive alcohol consumption, and relapse of chronic viral hepatitis, whereas non-identifiable triggers do not have any clinically identifiable cause ( 21 23 ). The mechanism of inflammation is not very well-characterized.…”
Section: Pathophysiological Mechanisms In Aclfmentioning
confidence: 99%
“…Despite a tendency to decrease over time, GIB has been discussed as one of the precipitating events for AD and ACLF. [11][12][13][14][15] In the CANONIC and the PREDICT study, the number of GIB showed no significant differences between AD and ACLF patients. 8,11 Only GIB with hypovolemic shock was found significantly more often in ACLF patients.…”
Section: Association Between Variceal Bleeding and Aclf Bleeding As P...mentioning
confidence: 85%
“…31,32 However, acute variceal bleeding (AVB) has been described in many studies as a well-known trigger of ACLF. 11,12,18,33 and severe GIB has been proven to have a significant impact on ACLF development 34,35 (►Table 1).…”
Section: Association Between Variceal Bleeding and Aclf Bleeding As P...mentioning
confidence: 99%